Identification of transcriptome characteristics of granulosa cells and the possible role of UBE2C in the pathogenesis of premature ovarian insufficiency - Dan Liu; Xiaohong Guan; Wenqiang Liu; Yanping Jia; Hong Zhou; Chenxiang Xi; Mei Zhao; Yuan Fang; Li Wu; Kunming Li (BMC, 2023)
Abstract Background Premature ovarian insufficiency (POI) is an important cause of infertility characterized by the functional decline of the ovary. Granulosa cells (GCs) around oocytes are critical for folliculogenesis, and GC dysfunction is one of the important etiologies of POI. The aim of this study was to explore the potential biomarkers of POI by identifying hub genes and analyze the correlation of biomarkers with immune infiltration in POI using RNA profiling and bioinformatics analysis. Methods RNA sequencing was performed on GCs from biochemical POI (bPOI) patients and controls. Differential expression analysis and weighted gene co-expression network analysis (WGCNA) were used to explore the candidate genes. qRT‒PCR was performed to verify the expression of hub genes. Western blot, Cell Counting Kit-8, 5‐ethynyl‐2'‐deoxyuridine (EdU) assays, TUNEL (TdT-mediated dUTP Nick-End Labeling) and flow cytometry analysis were used to validate the possible role of ubiquitin-conjugating enzyme 2C (UBE2C) in POI. CIBERSORT was adopted to explore immune cell infiltration and the correlation between UBE2C and immune cells in bPOI. Results Through analysis of differentially expressed genes (DEGs) and WGCNA, we obtained 143 candidate genes. After construction of the protein‒protein interaction (PPI) network and analysis with Cytoscape, 10 hub genes, including UBE2C, PBK, BUB1, CDC20, NUSAP1, CENPA, CCNB2, TOP2A, AURKB, and FOXM1, were identified and verified by qRT‒PCR. Subsequently, UBE2C was chosen as a possible biomarker of POI because knockdown of UBE2C could inhibit the proliferation and promote the apoptosis of GCs. Immune infiltration analysis indicated that monocytes and M1 macrophages may be associated with the pathogenesis of POI. In addition, UBE2C was negatively correlated with monocytes and M1 macrophages in POI. Conclusions This study identified a hub gene in GCs that might be important in the pathogenesis of POI and revealed the key role of UBE2C in driving POI. Immune infiltration may be highly related with the onset and etiology of POI.